Penggunaan Silika Gel-GPTMS-DMA untuk Analisis Ion Bromida (Br⁻) secara Kromatografi Ion - Vitratul Wirza; Budhi Oktavia (Lembaga Yasin AlSys, 2025)
The limited research on the use of glycidoxypropyltrimethoxysilane–dimethylamine (GPTMS–DMA) modified silica gel as a stationary phase in ion chromatography serves as the background of this study, particularly in the context of bromide ion (Br⁻) analysis, which poses health risks due to its potential to form carcinogenic bromate compounds upon reacting with disinfectants. This study aims to evaluate the effectiveness of GPTMS–DMA modified silica gel as a stationary phase in ion chromatography columns for bromide ion separation. A quantitative experimental laboratory method was employed using bromide solutions at concentrations of 100 ppm, 200 ppm, and 300 ppm. Analysis was conducted using High Performance Liquid Chromatography (HPLC) equipped with a UV detector and eluents consisting of Na₂CO₃ and NaHCO₃ at concentrations of 0.1 M, 0.05 M, and 0.01 M. The results showed that the 0.1 M Na₂CO₃ eluent delivered the best performance, producing sharp chromatographic peaks, high intensity, and a stable baseline. The obtained regression equation was y = 0.0002x + 0.0807 with a determination coefficient R² > 0.9992, indicating excellent linearity. The Limit of Detection (LOD) was 12.28 ppm, and the Limit of Quantification (LOQ) was 40.93 ppm, demonstrating adequate sensitivity. The study concludes that GPTMS–DMA modified silica gel has high potential as an efficient and cost-effective alternative stationary phase for bromide ion separation. Its implications include theoretical contributions to the development of hybrid materials for ion separation and practical applications in producing more affordable ion chromatography columns. The research also opens opportunities for further studies on the separation of other inorganic ions using similar materials.